2021
DOI: 10.1136/bmjopen-2021-056260
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific prevalence of metabolic-associated fatty liver disease among government employees in Tianjin, China: a cross-sectional study

Abstract: ObjectivesTo explore the prevalence and risk factors of metabolic-associated fatty liver disease (MAFLD) in Tianjin government employees of different genders.DesignCross-sectional study.SettingHealth Management Center of Tianjin Union Medical Center.Participants16 924 government employees (59.6% male).MeasuresUltrasound liver examination was performed to determine whether there is fat accumulation in the organ. Participants’ weight and height were measured, and body mass index (BMI) was calculated.ResultsThe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…Previous studies noted that women over the age of 60 had a higher prevalence of MAFLD than men, possibly influenced by menopause in women ( 30 , 31 ). Moreover, the peak prevalence of MAFLD was between the ages of 18 and 50 in other studies, which supported our suggestion that middle-aged people were more likely to develop MAFLD compared with older people ( 32 , 33 ). Possible reasons for a higher MAFLD prevalence in younger patients were as follows: middle-aged people were more susceptible to sedentary lifestyles, obesity, and stressful socioeconomic status, which increased MAFLD risk; elderly patients experienced an increased overall mortality partially caused by fatty liver; and the deceased patients were excluded from the MAFLD population ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies noted that women over the age of 60 had a higher prevalence of MAFLD than men, possibly influenced by menopause in women ( 30 , 31 ). Moreover, the peak prevalence of MAFLD was between the ages of 18 and 50 in other studies, which supported our suggestion that middle-aged people were more likely to develop MAFLD compared with older people ( 32 , 33 ). Possible reasons for a higher MAFLD prevalence in younger patients were as follows: middle-aged people were more susceptible to sedentary lifestyles, obesity, and stressful socioeconomic status, which increased MAFLD risk; elderly patients experienced an increased overall mortality partially caused by fatty liver; and the deceased patients were excluded from the MAFLD population ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the peak MAFLD prevalence occurred earlier in males (approximately 51 years of age) than in females (approximately 66 years of age). This finding has also been reported ( 49 51 ). Potential reasons for the high prevalence in middle-aged males include sociocultural issues, life stress, and alcohol consumption in middle age.…”
Section: Discussionsupporting
confidence: 89%
“…For some high-risk populations such as employed adults with frequently irregular lifestyles and shift work [ 3 , 4 ], the MAFLD is of concern. As is reported, the prevalence of MAFLD in employed adults is around 40% in China [ 5 7 ]. Stacks of evidence suggested that MAFLD is closely associated with poor health consequences, such as cirrhosis and hepatocellular carcinoma [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 98%